Peran Mahasiswa Dalam Pemberdayaan Masyarakat Jorong Batang Gunung Dalam Program Pengembagan Pendidikan dan Sosial: - Fitri Yani; Annaisaburi Nasution; Sona Satriana; Aida Lasmi; Sutan Perlindungan (Reslaj : Religion Education Social Laa Roiba Journal, 2023)
eaching and learning activities have now begun to be carried out face-to-face/offline. This is because the condition has begun to recover from Covid-19. The Regular Community Service KKN held in Jorong Batang Gunung, Kenagarian Koto Gunung, Lembah Melintang District, West Pasaman Regency has the aim of providing knowledge and understanding to the local community about the importance of education and health in the current situation. The programs that support it are teaching in elementary schools, Let’s Study activities and Keeping Clean activities to foster learning motivation in children. The method used in this program is to provide exclusive assistance in the learning process and apply fun learning methods, for example by providing and presenting material through songs, games, quizzes and so on. So that children are able to learn and understand the material calmly and pleasantly. Keywords: Let's Study, Learning Assistance